Disaster Prevention and Management: A Critical Review of The Literature - Nazaruddin Ali Basyah; Muhammad Syukri; Irham Fahmi; Ismail Ali; Zulfadhli Rusli; Elva Sesioria Putri (Postgraduate, University of Mataram, 2023)
This article explores disaster management, focusing on ethical considerations and fair allocation of relief resources in public health disasters. Disasters require emergency resources to aid and protect affected populations, raising ethical questions about fair allocation of relief funds for speedy recovery. Research in crisis situations presents moral dilemmas, balancing the ethical obligation to protect study participants' interests with the necessity for research. This literature review examines these topics in disaster response and recovery, emphasizing virtues such as caution, courage, justice, stewardship, vigilance, resilience, selfless charity, and communication in catastrophe response. Using the PRISMA method, relevant peer-reviewed articles were selected, highlighting the need for further research in disaster mitigation and management. The paper emphasizes the importance of justice and ethics in crisis situations, underlining the fundamental role of ethics in driving societal changes. Intending to enhance disaster management, this study introduces ethical concepts to stimulate discussions among disaster responders and managers. As an original contribution, this paper provides valuable insights for disaster management students and educators, significantly contributing to understanding the relationship between disaster prevention and management, and offering relevant recommendations to enhance disaster management outcomes.